Verona liver day: Data of liver health from the Arena. (March 2023) - Sacerdoti, D.; Paon, V.; Ieluzzi, D.; Dalbeni, A.; Mantovani, A.; Perusi, G.; Zoncapè, M.; Famà, F.; Bevilacqua, M.; Cattazzo, F.; Stupia, R.; De Marco, L.; et al.
Abstract : Background: Liver diseases affect millions of people worldwide, with different etiologies between countries. The incidence of viral hepatitis is waning as a result of advances in prevention and new therapies. In contrast, with the improvement in living standards, the incidence of metabolic liver diseases including non-alcoholic fatty liver disease and alcohol-related liver disease is set to rise. Aim: On the 14th of May 2022 the Liver Unit Team of Azienda Ospedaliera Universitaria Integrata of Verona organized a "Liver Day" for the general population with educational and preventive aim. Using a mobile medical center with an ultrasound scanner, a fibroscan and HCV test kits, 110 people were visited and screened. Many other people had only information. Results: From the anamnestic data collected, alcohol consumption (> 100 g/week) was detected in 36.5%, hypertension in treatment in 39%, dyslipidemia in 35.6%, type 2 diabetes in 6.7% of our population. We confirmed HCV Ab in 6 patients, nobody with unknown HCV was detected. Based on these collected data, a sample of people was subjected to a fibroscan method and/or an abdominal ultrasound and 40% had steatosis. MAFLD was detected in 28.7% of cases. Liver stiffness (LS) measured with Fibroscan was 5.11±1.28 kPa; only one patient had LS> 8 kPa. LS was higher in MAFLD group. MAFLD patients (n=30) had higher BMI (median BMI 28.3 (IQR 5.10) vs 23.7 (IQR 4.50) and higher waist circumference (median 99±14.18 vs 87±15.20 cm). Conclusions: Data from Verona general population confirms the relevant prevalence of risk factors (alcohol and MAFLD) which can lead to chronic liver disease.